Correlations between magnetic resonance spectroscopy alterations and cerebral ammonia and glucose metabolism in cirrhotic patients with and without hepatic encephalopathy. Issue 12 (27th July 2007) - Weissenborn, Karin; Ahl, Björn; Fischer-Wasels, Daniela; van den Hoff, Joerg; Hecker, Hartmut; Burchert, Wolfgang; Köstler, Herbert
Abstract : Background: Hepatic encephalopathy is considered to be mainly caused by increased ammonia metabolism of the brain. If this hypothesis is true, cerebral glucose utilisation, which is considered to represent brain function, should be closely related to cerebral ammonia metabolism. The aim of the present study was to analyse whether cerebral ammonia and glucose metabolism in cirrhotic patients with early grades of hepatic encephalopathy are as closely related as could be expected from current hypotheses on hepatic encephalopathy. Methods: 13 N-ammonia and 18 F-fluorodesoxyglucose positron emission tomography, magnetic resonance imaging and magnetic resonance spectroscopy (MRS) were performed in 21 cirrhotic patients with grade 0–1 hepatic encephalopathy. Quantitative values of cerebral ammonia uptake and retention rate and glucose utilisation were derived for several regions of interest and were correlated with the MRS data of the basal ganglia, white matter and frontal cortex. Results: A significant correlation between plasma ammonia levels and cerebral ammonia metabolism, respectively, and MRS alterations could be shown only for white matter. In contrast, MRS alterations in all three regions studied were significantly correlated with the glucose utilisation of several brain regions. Cerebral ammonia and glucose metabolism were not correlated. Conclusion: Increase of cerebral ammonia metabolism is an important but not exclusive causal factor for the development of hepatic encephalopathy.